Gold mineralization related to Proterozoic cover in the Congo craton (Central African Republic): A consequence of Panafrican events. (June 2020) - Kpeou, José; Béziat, Didier; Salvi, Stefano; Estrade, Guillaume; Moloto-A-Kenguemba, Gaétan; Debat, Pierre
Abstract: Despite its high endowments, the gold mining potential of Central African greenstone belts is seemingly underrated when compared to equivalent belts in neighbor West Africa. This is probably because, over the past half century, only minor exploration efforts were ever made in this region. In the southwest of the Central African Republic, near the locality of Moboma, gold-bearing quartz veins are hosted in greenschist facies Paleoproterozoic formations that are intruded by numerous dolerite dykes. These rocks occur in a strongly deformed terrane that marks the front of the Panafrican Oubanguides nappe, developed during an E-W regional shortening. Presence of multiple banding indicates repeated reactivation of the quartz veins and circulation of H2 O–CO2 –NaCl fluids, similar to those characterizing typical orogenic gold-bearing settings. Fluid inclusion petrography and microthermometry permitted to distinguish two different fluids: one, aqueous-carbonic, circulated at relatively high temperature (Th = 250–270 °C) and was responsible for the main stage of Au deposition; a second fluid of low-salinity trapped in microcracks and in a late quartz generation, interpreted as meteoric, precipitated silver-poor native gold. At a later stage, supergene alteration caused the formation of discrete gold nuggets in the upper levels of the mineralization. The competent nature of the dolerite dykes and quartzite intersected by these quartz veins contributed to focus rock fracturing, localizing fluid circulation and the mineralization. The alteration assemblage developed in the veins is equivalent to that found in the dolerite dykes, which was dated at 571 Ma, thus pointing to a Panafrican age for the mineralization at Moboma. Highlights: Rare geological and mineralogical data on a quartz vein-hosted gold deposit from the Central African Republic. Fluid inclusion evidence for multiple fluid flow. Genetic model for the formation of the quartz veins. Indirect dating of the emplacement of mineralization. Model proposing structural relationship between the Panafrican Oubanguides nappe and orogenic gold mineralization.